Search for exclusive Higgs and Z boson decays to ϕγ and ργ with the ATLAS detector - The ATLAS collaboration; M. Aaboud; G. Aad; B. Abbott; O. Abdinov; B. Abeloos; S. H. Abidi; O. S. AbouZeid; N. L. Abraham; H. Abramowicz; H. Abreu; R. Abreu; et al. (Journal of High Energy Physics, 2018)
Abstract A search for the exclusive decays of the Higgs and Z bosons to a ϕ or ρ meson and a photon is performed with a pp collision data sample corresponding to an integrated luminosity of up to 35.6 fb−1 collected at s=13 $$ \sqrt{s}=13 $$ TeV with the ATLAS detector at the CERN Large Hadron Collider. These decays have been suggested as a probe of the Higgs boson couplings to light quarks. No significant excess of events is observed above the background, as expected from the Standard Model. Upper limits at 95% confidence level were obtained on the branching fractions of the Higgs boson decays to ϕγ and ργ of 4.8 × 10−4 and 8.8 × 10−4, respectively. The corresponding 95% confidence level upper limits for the Z boson decays are 0.9 × 10−6 and 25 × 10−6 for ϕγ and ργ, respectively.